Analisis Hukum Pelaksanaan Perjanjian Kerjasama Pelayanan Administrasi Operasional Jasa Pemanduan Kapal Antara PD. Pelabuhan Dumai Bersemai (BUMD) dengan PT. Pelabuhan Tiga Bersaudara Yang Berakibat Wanprestasi - Citra Rahmawati Lubis; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Agreement on cooperation made between PD. Dumai Bersemai Port (BUMD) with PT. TigaBersaudara Port has fulfilled the legal requirements of an agreement as stipulated in Article 1320 of theCivil Code. But over time, this agreement has become null and void, because the second party is PD. DumaiBersemai Port canceled the agreement, and unilaterally decided the agreement, this happened because PT.Tiga Bersaudara Port on the implementation of the practice of cooperation agreements between PD. DumaiBersemai Port is seeded with PT. Tiga Bersaudara Port did not side with PT. Dumai Bersemai Port as thesecond party in this agreement, and PT. Tiga Bersaudara Port has defaulted by not paying a profit sharingfund of 7.5% to PD. Dumai Bersemai Port.The author sets the main problem as follows about whether the factors causing the default betweenPD. Dumai Bersemai Port (BUMD) with PT. The Tiga Bersaudara Port and what are the legalconsequences of not implementing a cooperation agreement between PD. Dumai Bersemai Port (BUMD)with PT. Tiga Bersaudara Port.This writing when viewed from the type of research is classified as sociological legal research andcan also be said as a field research that is reviewing the applicable legal provisions and what happens inreality in the community or in other words a study conducted on actual reality or real conditions occur inthe community with the intention to find out and find the facts and data needed collected then go to theidentification of problems which ultimately lead to problem solving. Whereas if viewed from its nature, thiswriting is descriptive analysis, which means that the research intended to provide a detailed, clear andsystematic description of the main research problems.From the results of research Factors that cause the occurrence of default between PD. DumaiBersemai Port (BUMD) with PT. Tiga Bersaudara Port because PT. Tiga Bersaudara Port does not share asharing fund of 7.5% of each revenue from ship scouting services carried out by PT. Tiga Bersaudara Port,so that PD. Dumai Bersemai Port carries out unilateral termination of the Cooperative Service CooperationAgreement on Ship Guiding Services Operations while the legal consequences of not implementingcooperation agreements between PD. Dumai Bersemai Port (BUMD) with PT. Tiga Bersaudara Port thatthere had been a unilateral termination of the contract by the Administrative Services CooperationAgreement of the Ship Guiding Service in the Special Terminal of PT. Sari Dumai Sejati, PT. Semen Padangand PT. Pacific Indopalm in Class 1 Dumai Compulsory Waters, the parties agreed to remind themselves ofa special bond contained in an agreement.